2021
DOI: 10.1039/d1cc00354b
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing affinity-based protein profiling to reveal a novel target of nintedanib

Abstract: Nintedanib (BIBF1120), a triple angiokinase inhibitor, was first approved for idiopathic pulmonary fibrosis (IPF) therapy and also efficacious for lung carcinoma, interstitial lung diseases, far beyond its inhibition of VEGFR/PDGFR/FGFR....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In addition to the three target proteins mentioned above, a diverse of different studies have shown that chemical proteomics is an excellent and powerful technique for discovering direct protein-ligand interactions [2]. Validation revealed that tripeptidase 1 (TPP1) is one of the direct targets that may be responsible for the multiple actions of nintedanib.…”
Section: Tpp1mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the three target proteins mentioned above, a diverse of different studies have shown that chemical proteomics is an excellent and powerful technique for discovering direct protein-ligand interactions [2]. Validation revealed that tripeptidase 1 (TPP1) is one of the direct targets that may be responsible for the multiple actions of nintedanib.…”
Section: Tpp1mentioning
confidence: 99%
“…Nintedanib was approved by the EMA in 2014 for the treatment of adult patients with advanced, metastatic and locally recurrent NSCLC. Chen's team [2] used an affinity-based protein profiling (AfBPP)-based chemical proteomic strategy for the target identification of nintedanib and identified TPP1 as one of its direct targets. Patients with systemic sclerosis-associated ILD can use nintedanib to slow down the decline in lung function.…”
Section: Introductionmentioning
confidence: 99%